Cognitive Difficulties, Mental Fatigue and Psychological Well-being of Women with Polycystic Ovary Syndrome - Zahid, Haieqa; Javed, Aiman (Clinical and Counselling Psychology Review, 2025)
Polycystic ovary syndrome (PCOS) is a common health issue in 52 percent of Pakistani women and linked with cognitive impairments and mental fatigue, but its psychological consequences have not been studied in-depth. This research seeks to investigate the connection between cognitive difficulties, mental fatigue and psychological wellbeing among PCOS women, to gain more insight into the psychological effect of the syndrome, and to guide its interventions that could improve their psychological health. A sample of 60 women aged 18-45 years was selected out of PCOS diagnosed women in both the private and public hospitals in Punjab, Pakistan. The research tools used in the study were as follows; Demographic Questionnaire, Cognitive Failure Questionnaire, Mental Fatigue Scale and Ryff’s Psychological Well Being Urdu Scale. The correlational analysis found that, both mental fatigue and cognitive difficulties had negative correlations with psychological well-being. Regression analysis also indicated that poor psychological wellbeing among the PCOS women was largely predicted by mental fatigue. In this study, it is demonstrated that lower degree of psychological wellbeing is related to the presence of cognitive difficulties and mental fatigue in women with PCOS, and such a result is predicted by mental fatigue to the greatest extent.